COVID-19 vaccine hesitancy: a survey in a population highly compliant to common vaccinations. Issue 10 (3rd October 2021) - Fedele, Flora; Aria, Massimo; Esposito, Valeria; Micillo, Maria; Cecere, Gaetano; Spano, Maria; De Marco, Giulio
ABSTRACT: Vaccination is a key protective factor against COVID-19. Some vaccines have already received emergency authorization from Health Agencies, but growing skepticism and vaccine hesitancy will probably affect COVID-19 vaccination campaigns. In the attempt to shed light on this issue, we conducted an online survey in a population of parents referring to 4 pediatric practices in Naples, Italy in whom we evaluated potential vaccine acceptability in relation to socio-demographic characteristics, perception of personal health and of the impact of COVID-19, and attitudes toward general vaccination practices. Vaccination rates were analyzed also in the corresponding pediatric population. Almost 27% of participants declared they were in favor of vaccinations, and in fact real life vaccination rates in children exceeded the national mean. Only 26.5% of respondents declared they would receive COVID-19 vaccine. Vaccine refusal was attributed to safety concerns in 76% of parents. Specific vaccine attributes further reduced the acceptance rate. Female gender, younger age and lower education level were associated with non-adherence to vaccination. Among extrinsic factors of COVID-19 vaccination, only information from National Health Authorities was significantly associated to vaccine acceptance. The rate of potential COVID-19 vaccine acceptability was very poor in our population of parents. Vaccine hesitancy was mainly due to safety concerns. Demographic and educational factors were correlated to vaccine acceptability. Health education and communication strategies are needed to achieve large-scale vaccine acceptability and finally herd immunity.